Understanding injuries in sports: Self-reported injury and perceived risk of injury among adolescents - Travert, M.; Maiano, C.; Griffet , J. (European Review of Applied Psychology, 2017)
Although exposure and perceived risk of injury in sports among adolescents is a well-known phenomenon today, their understanding remains poorly explored. Objective: This study examines the relationships between demographics, sport motives, and sport-related characteristics in a sample of French adolescents involved in sports. Methods: The sample included 394 adolescents involved in sports, between 13 and 19 years old. The adolescents filled out a questionnaire requesting information about their age, sex, sport motives, sport-related characteristics, the number of injuries, and perceived risk of injury in their preferred sport. Results: The findings showed that the number of injuries was related to age, sex, type of sport and the participant's motives. The will to play to the limit increased with the exposure to injury. Participation in risky sports and the will to play to the limit were predictors of the adolescents` risk of exposure to sports injuries. Time devoted to sports appears to be a confounding factor. Moreover, boys exhibited higher number of injuries than girls, and they perceived their preferred sport as riskier. Conclusion: Exposure to the risk of injury in sports and the exacerbated perception of that risk may provide a means of enhancing one's self-image, procuring an emotional experience, and constructing one's masculinity.